Cooperation of metropolitan areas - case study metropolis cooperation Berlin - Hamburg - Jörg Knieling (European Regional Science Association (ERSA), 2002)
For metropolitan regions on the national and even more on the international level there is a specific context of competition, especially in terms of economic development but also referring to quality of life. At the same time, metropolitan regions are in the need to cooperate with each other: - synergies: neighbouring metropolitan regions are looking for synergies through networking, e. g. reaching a higher level of public infrastructure by specialisation or concentration, - problem-solving: exchange between metropolitan regions is supposed to lead to higher standards of problem-solving , e.g. in traffic, public administration or suburbanisation. - lobbying: together metropolitan regions can try to create a political lobby in order to gain support for their specific aims on the national or European level. But on the way to a successful "competitive cooperation" between metropolitan regions specific restrictions remain, which have to be overcome: - policy dimension: each metropolitan region has its own political agenda with topics of different importance. Cooperation has to identify interests of importance for all cooperants involved. - politics dimension: actors can vary because of different political majorities, these majorities can change during a cooperation process, or there are different regional cultures influencing the cooperation, - polity dimension: metropolitan regions show various forms of institutional organisation, some are organised in a more formal way, others more or less informally. Consequently, there are, e. g. different competences of the regional bodies. The paper to be presented describes the chances and restrictions of cooperation between metropolitan regions in a combination of a theoretical and an empirical approach. The Berlin - Hamburg metropolitan cooperation is presented as a case study. In addition, experiences of the German metropolitan regions' network are integrated: - The Berlin-Hamburg metropolitan cooperation formally started in May 2001, dealing with a wide range of subjects. In December 2001 a status report was launched (see enclosure). - The German metropolitan regions' network is financed by the Ministry of Spatial Planning. It has been working since July 2001. Its agenda includes identifying specific positions of German metropolitan regions in the context of national and European (ESDP-) policy.
Keywords: 330